A quantitative study on female sex workers’ mental health in Germany - Kroehn-Liedtke, Franziska; Kalinowski, Olivia; Kaya, Gizem; Lotysh, Anastasiia; Mihaylova, Hristiana; Sipos, Krisztina; Strunk, Annika; Zerbe, Lena; Rössler, Wulf; Schouler-Ocak, Meryam (Frontiers in Public Health, 2025)
IntroductionSex workers provide sexual services in exchange for monetary compensation, encompassing a range of activities such as escorting, pornography and street-based or online sex work. Individuals doing sex work are frequently referred to as a vulnerable group when it comes to their mental health. Despite the legality of sex work in Germany, there are significant risk factors associated with negative impact on the mental health, such as stigmatization, precarious working conditions and experienced violence. The aim of this study was to examine specific sex work settings. It was hypothesized that sex workers report high levels of structural stress and psychological distress and that specific work-related factors (e.g., stigma, safety concerns, interactions with clients) would significantly predict mental health outcomes.MethodsSince the majority of sex workers is female, the mental health of 403 women engaged in sex work was assessed in this study using quantitative interviews with standardized instruments. To acquire prevalence rates of mental disorders and compare them with others engaged in high-stress environments a control group of 157 female social workers was interviewed. To investigate the hypotheses descriptive analyses, Chi2-tests, logistic regression and cluster analysis were used. This study employs a cross-sectional design to equally reflect the different characteristics of the heterogeneous groups such as age, educational level, background and different work settings.ResultsAs expected, mental disorder prevalences were higher among sex workers than in the general population and in the control group. However, logistic regression identified risk factors for mental illness, including residence status (OR = 1.33, CI = 1.05–1.69, p = 0.018; Ref = no), homelessness (OR = 0.11, CI = 0.02–0.48, p = 0.003; Ref = yes), income status (OR = 0.50, CI = 0.25–0.97, p = 0.042; Ref = low), perceived threat or control (OR = 0.15, CI = 0.03–0.84, p = 0.030; Ref = no) and work-related stress (OR = 2.83, CI = 1.11–7.18, p = 0.029; Ref = low) emerging psychological and structural stressors as crucial factors.DiscussionThese findings highlight the need for special health care services and improved economic and legal security of sex workers. Policy changes focusing on improved medical and psychological care and structural interventions aiming economic and social needs while fostering societal acceptance and understanding are required.